Evaluasi Komputasi (E)-2-(benzoxazol-2-yl)-3-phenylacrylonitrile (S6) sebagai Sensor Kolorimetri Ion Sianida Berbasis Mekanisme Ganda - Rahmawati Rahmawati; Syarifa Wahidah Al Idrus (MASALIQ, 2026)
Structural modification of the sensor is necessary to improve the sensitivity of cyanide ion (CN⁻) detection, which has a threshold of 1.9 × 10⁻⁶ M according to WHO. This study aims to evaluate the potential of (E)-2-(benzoxazol-2-yl)-3-phenylacrylonitrile (S6) as a benzoxazole-based cyanide ion sensor through a computational approach. This study used DFT/B3LYP/6-31G(d) and TD-DFT methods to analyze electronic properties, molecular interactions, absorption shifts, binding constants, detection limits, and electrostatic potential maps. The results show that the addition of a dicyanovinyl group to S6 produced a HOMO energy of -5.9247 eV, a LUMO energy of -3.2493 eV, and an energy gap (ΔE) of 2.6754 eV. The interaction of S6 with CN⁻ formed the S6-CN complex through nucleophilic addition and N-H···N≡C hydrogen bonding, which narrowed ΔE to 2.3829 eV and induced a bathochromic shift of 69 nm from 352 nm to 421 nm. The binding constant k_bind value of 1.25 × 10⁴ M⁻¹ and detection limit of 1.4 × 10⁻⁵ M indicate that S6 has 31-fold higher sensitivity than S5. The ESP map confirms that N-H, with a value of +45.2 kcal/mol, acts as the active site. The conclusion of this study affirms that the dual mechanism in S6 supports high selectivity toward CN⁻ and contributes to the rational design of benzoxazole-based cyanide sensors.